Effects consistent with behavioral contrast during a multiple schedule for discrimination training on mands for attention. (8th December 2022) - Bayaruga, Marylou; Pyles, David A.
Abstract: This study used a multiple schedule to assess the effects of an S+ or S‐ in the absence of rules on excessive mand rates with three school‐aged children with disabilities and assessed possible contrast effects occurring in conjunction with the intervention. Each of the three participants was exposed to the presence or absence of an S‐ (black baseball cap). When it was worn, mand approach rates decreased for all three participants; conversely, mand rates increased to twice the baseline rates when the experimenter was not wearing the black baseball cap. Generalization probes conducted for one of the three caregivers showed similar changes when the caregiver wore the cap. Results suggest that effects consistent with positive behavioral contrast occurred with all participants.